An empirical investigation of the reasons of financial needs and preference of Islamic banking customers in Türkiye - Doğan Başar, Berna; Rençber, Ömer Faruk; Ekşi, İbrahim Halil (Afyon Kocatepe Üniversitesi)
Many interest-free financial organs are operating in a similar system all over the world, especially in Muslim countries. Islamic banks are banks that operate in the financial sector, support the real economy, and offer banking services. Islamic banks collect funds from savers, make them available in industry and trade sectors according to interest-free financing ethics and share profit or loss with savers. Alternative financing systems are one of the issues discussed in recent years to reduce the problems arising from the traditional banking system, which has become controversial especially with the recent crises. One of these alternatives is Islamic finance practices. As in all the world, the rising market share in Türkiye is increasing interest in the bank. This study aims to guide banks in product development by using data mining techniques in Islamic banking in terms of being a service enterprise. For this purpose, a face-toface survey was conducted with 212 customers registered at 5 branches of an Islamic bank. In the study in which decision tree methodology is conducted, the satisfaction, needs, and expectations of the bank are determined according to the different characteristics of the customers (socio-economic factors, financial and Islamic literacy levels etc.). From this point of view, product and policy development suggestions were brought to Islamic banks according to customer characteristics.

Birçok faizsiz finans kurumu, başta Müslüman ülkeler olmak üzere tüm dünyada benzer bir sistem içinde faaliyet göstermektedir. Ġslami bankalar, finans sektöründe faaliyet gösteren, reel ekonomiyi destekleyen ve bankacılık hizmetleri sunan bankalardır. Ġslami bankalar tasarruf sahiplerinden fon toplar, bunları faizsiz finansman etiğine göre sanayi ve ticaret sektörlerinde kullanılabilir hale getirir ve kâr veya zararı tasarruf sahipleriyle paylaşır. Alternatif finansman sistemleri, özellikle son dönemde yaşanan krizlerle birlikte tartışmalı hale gelen geleneksel bankacılık sisteminden kaynaklanan sorunları azaltmak için son yıllarda tartışılan konulardan biridir. Bu alternatiflerden biri de Ġslami finans uygulamalarıdır. Tüm dünyada olduğu gibi Türkiye'de de artan pazar payı bankaya olan ilgiyi artırıyor. Bu çalışma, bir hizmet işletmesi olması açısından Ġslami bankacılıkta veri madenciliği tekniklerini kullanarak ürün geliştirmede bankalara rehberlik etmeyi amaçlamaktadır. Bu amaçla, Ġslami bir bankanın 5 şubesinde kayıtlı 212 müşteri ile yüz yüze anket yapılmıştır. Karar ağacı metodolojisinin uygulandığı çalışmada, müşterilerin farklı özelliklerine (sosyo-ekonomik faktörler, finansal ve Ġslami okuryazarlık düzeyleri vb.) göre bankanın memnuniyet, ihtiyaç ve beklentileri belirlenmektedir. Bu açıdan Ġslami bankalara müşteri özelliklerine göre ürün ve politika geliştirme önerileri getirilmiştir.
Türkiye'deki İslami banka müşterilerinin mali iİhtiyaçlarının ve tercihlerinin ampirik araştırılması
Keywords: Participation Bank; Customer Preference; Empirical Review; Katılım Bankası; Müşteri Tercihi; Ampirik İnceleme